Assessing the state of care for Huntington disease in the United States: Results from a survey of practices treating Huntington disease patients. (2022) - Seeberger, Lauren; Corey-Bloom, Jody; O'Brien, Michael; Slowiejko, Diana; Schlang, Danielle; Booth, Marika S.; Ann Griffin, Beth; Chen, Peggy G.; ,
Highlights: This research study of 156 US healthcare practices is the first of its kind to include non-specialty neurologists and primary care physician practices, as well as academic practices surveyed about their treatment of Huntington disease patients. One-half of HD practices surveyed saw 2 or less patients per month, while about one quarter of practices saw 1 or more patients per week. HD care appears to be inconsistently applied across the US. Differences were noted in a practice's ability to provide care navigators, genetic counselors, or psychologists/psychiatrists, or to conduct pre-visit screening of their patients, or routinely monitor weight. Practices seeing a higher volume of HD patients and ones led by movement disorder-trained neurologists, tended to be better equipped to provide a broader range of multi-disciplinary care. Abstract: Background: No study to date has thoroughly examined US Huntington disease (HD) care delivery in a variety of clinic settings by HD specialists and non-specialists. Objective: To obtain a clearer understanding of current care structure and delivery of care through a survey of representative US physicians treating HD patients. Methods: We designed and fielded a survey of 40 closed-ended evaluative items and one open-ended item to a sample of 339 US practices. Unique to this survey was the inclusion of non-specialists. Results: Responses were received from 156 practices (overall response rate 46.02 %), with 52.6 % from academic sites, 35.3 % from private practices, and 12.2 % from the VA. More than half (63.5 %) of the practice leads were movement disorder trained or Directors of HDSA Centers of Excellence and 58.3 % had an HD or multidisciplinary care clinic. However, 48.7 % of the practices saw 1–25 HD patients, 28.2 % saw 26–100 HD patients, and 23.1 % served over 100 HD patients annually. Most practices (>69 %) reported having difficulty providing social work, genetic counseling, care coordination and psychologists/psychiatrists. Increased HD practice size was associated with higher rates of pre-visit screenings, care navigator/care coordinators, routine monitoring of weight, and provision of genetic counseling by genetic counselors. Conclusions: Not surprisingly, we found that HD care was inconsistently applied across the US. Practices led by neurologists trained in movement disorders, and higher HD volume practices, tended to be better equipped to provide multi-disciplinary staffing and procedures as compared to those with fewer numbers of HD patients.